Diurnal Characteristics of Trapped Mountain Waves over the Foothills of Western Nepal Himalaya - Regmi, Ram P. (Journal of Institute of Science and Technology, 2015)
Late wintertime diurnal variation and spatial distribution of mountain wave excitations over the Mt. Devchuli range and its surrounding areas have been numerically simulated with the application of Weather Research and Forecasting (WRF) Modeling System. The study reveals that the region holds low-level trapped mountain waves almost all the time. The waves are confined below the stratified layer at about 3km above the mean sea level. Wave excitation over the region is highly active during the afternoon time whereas it remains at minimum level during the late morning time. These waves pose significant risk for low-level aviation and parachuting activities. Journal of Institute of Science and Technology, 2015, 20(1): 102-106